Marketing Content Analysis of Korean Drama Streaming Platforms: Social Network Analysis on Twitter - Novi Kartikasari; Rita Ambarwati; Alshaf Pebrianggara (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2023)
The primary purpose of this research is to assist in providing input for digital marketing of VIU and iQiyi from the results of Twitter users' tweets, as well as to find out the focus of discussions from Twitter users on VIU and iQiyi Video Streaming Platforms. This research collected tweet data from June 2020 to June 2022. The existing data is then carried out in the preprocessing stage with a combination of methods so that there is no noisy data as a maximum. Furthermore, the final step is to analyze the results of the images visualized using Gephi. The results of the data visualization show that each of the data withdrawal criteria is responded to by users so that this phenomenon can provide input for the future in improving existing marketing strategies on the VIU and iQiyi video streaming platforms.